Peningkatan Efek Antiinflamasi Multikomponen Etorikoksib terhadap Penurunan TNF-α - Rahmadevi, Rahmadevi; Zaini , Erizal; Yuliandra , Yori (Journal of Pharmaceutical and Sciences, 2025)
Etoricoxib, a selective COX-2 inhibitor, is widely used for its anti-inflammatory effects but is associated with dose-dependent adverse events. Multicomponent formulations with coformers or solubilizing agents offer a potential strategy to improve efficacy while minimizing toxicity. This study aimed to evaluate the anti-inflammatory efficacy of pure etoricoxib and its multicomponent formulations with nicotinamide, N-methyl glucamine, and piperine using TNF-α as a coformer. A controlled laboratory experiment was conducted in Wistar rats using a carrageenan-induced granuloma pouch model. TNF-α levels were measured at baseline (0 hours) and at 6 hours post-treatment. Normality tests, two-way ANOVA, and Tukey HSD post-hoc analyses were applied to assess group differences and time effects. All treatment groups significantly reduced TNF-α levels compared to the control (p < 0.001). While pairwise comparisons between treatments were not statistically significant, the P4 formulation (etoricoxib–piperine) showed the most consistent reduction. P3 (etoricoxib–N-methyl glucamine) exhibited a near-significant difference from pure etoricoxib (P1), suggesting enhanced efficacy. The main effect of time confirmed the temporal decline of TNF-α (p = 0.0101), without significant group × time interaction. Multicomponent formulations, particularly those containing piperine and N-methyl glucamine, enhance the anti-inflammatory action of etoricoxib. These research support further development of bioenhanced etoricoxib as safer alternatives for antiinflammatory.